Interstellar formation of lactaldehyde, a key intermediate in the methylglyoxal pathway - Jia Wang; Chaojiang Zhang; Joshua H. Marks; Mikhail M. Evseev; Oleg V. Kuznetsov; Ivan O. Antonov; Ralf I. Kaiser (Nature Communications)
Abstract Aldehydes are ubiquitous in star-forming regions and carbonaceous chondrites, serving as essential intermediates in metabolic pathways and molecular mass growth processes to vital biomolecules necessary for the origins of life. However, their interstellar formation mechanisms have remained largely elusive. Here, we unveil the formation of lactaldehyde (CH3CH(OH)CHO) by barrierless recombination of formyl (HĊO) and 1-hydroxyethyl (CH3ĊHOH) radicals in interstellar ice analogs composed of carbon monoxide (CO) and ethanol (CH3CH2OH). Lactaldehyde and its isomers 3-hydroxypropanal (HOCH2CH2CHO), ethyl formate (CH3CH2OCHO), and 1,3-propenediol (HOCH2CHCHOH) are identified in the gas phase utilizing isomer-selective photoionization reflectron time-of-flight mass spectrometry and isotopic substitution studies. These findings reveal fundamental formation pathways for complex, biologically relevant aldehydes through non-equilibrium reactions in interstellar environments. Once synthesized, lactaldehyde can act as a key precursor to critical biomolecules such as sugars, sugar acids, and amino acids in deep space.